Show that \( 2 x+1 \) is a factor of \( 6 x^{3}-5 x^{2}-12 x-4 \). Then find the roots of \( 6 x^{3}-5 x^{2}-12 x-4=0 \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To show that \(2x + 1\) is a factor of \(6x^3 - 5x^2 - 12x - 4\), we can use polynomial long division or synthetic division. Let's start by determining \( x \) when \(2x + 1 = 0\): \[ 2x + 1 = 0 \implies 2x = -1 \implies x = -\frac{1}{2} \] Now, we substitute \(x = -\frac{1}{2}\) into the polynomial \(6x^3 - 5x^2 - 12x - 4\): \[ 6\left(-\frac{1}{2}\right)^3 - 5\left(-\frac{1}{2}\right)^2 - 12\left(-\frac{1}{2}\right) - 4 = 6\left(-\frac{1}{8}\right) - 5\left(\frac{1}{4}\right) + 6 - 4 \] \[ = -\frac{6}{8} - \frac{5}{4} + 6 - 4 = -\frac{3}{4} - \frac{5}{4} + 6 - 4 = -\frac{8}{4} + 2 = -2 + 2 = 0 \] Since substituting \(x = -\frac{1}{2}\) results in \(0\), this confirms that \(2x + 1\) is indeed a factor. Now, we perform synthetic division of \(6x^3 - 5x^2 - 12x - 4\) by \(2x + 1\) (or the root \(-\frac{1}{2}\)): \[ \begin{array}{r|rrrr} -\frac{1}{2} & 6 & -5 & -12 & -4 \\ & & -3 & 4 & 4 \\ \hline & 6 & -8 & -8 & 0 \\ \end{array} \] The result from synthetic division is \(6x^2 - 8x - 8\). We can now factor this quadratic: To factor \(6x^2 - 8x - 8\), we can either use the quadratic formula or factor it directly: Using the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{8 \pm \sqrt{(-8)^2 - 4 \cdot 6 \cdot (-8)}}{2 \cdot 6} \] \[ = \frac{8 \pm \sqrt{64 + 192}}{12} = \frac{8 \pm \sqrt{256}}{12} = \frac{8 \pm 16}{12} \] This gives us: \[ x = \frac{24}{12} = 2 \quad \text{and} \quad x = \frac{-8}{12} = -\frac{2}{3} \] Thus, the roots of the equation \(6x^3 - 5x^2 - 12x - 4 = 0\) are: 1. \(x = -\frac{1}{2}\) (from the factor \(2x + 1\)), 2. \(x = 2\), 3. \(x = -\frac{2}{3}\). In summary, the roots of the polynomial \(6x^3 - 5x^2 - 12x - 4 = 0\) are \(x = -\frac{1}{2}, 2, -\frac{2}{3}\).